Asymmetric Synthesis of a Pyrrolizidinone‐Based hNK1 Antagonist through Reductive Ring Contraction of a Six‐Membered Cyclic Nitronate. Issue 41 (27th September 2022) - Okladnikov, Ilya V.; Boyko, Yaroslav D.; Nelyubina, Yulia V.; Ioffe, Sema L.; Sukhorukov, Alexey Yu.
Abstract: A concise seven‐step asymmetric synthesis of MSD's potent hNK1 antagonist containing a pyrrolizidinone core bearing two fluorine‐substituted aryl groups was developed. The pyrrolizidinone unit was constructed by reductive recyclization of a properly functionalized cyclic nitronate, which was assembled by stereoselective [4+2]‐cycloaddition of a nitroalkene with a vinyl ether bearing a Whitesell's chiral auxiliary group. The configuration of the hNK1 antagonist, which was previously suggested based on bioactivity data, was confirmed by X‐ray analysis. The crystal structure features multiple weak interactions involving fluorine atoms that are also found in a complex with the hNK1 receptor simulated by molecular docking. Abstract : A seven‐step asymmetric synthesis of a potent hNK1 antagonist has been accomplished through a stereoselective reductive recyclization of a properly functionalized six‐membered cyclic nitronate.